2020
DOI: 10.1177/2332858419892575
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cross-Linguistic Contribution of Spanish and English Academic Language Skills to English Text Comprehension for Middle-Grade Dual Language Learners

Abstract: In this study, we examine the unique and shared contributions of Spanish and English core academic language skills (CALS) to English reading comprehension in a population of Spanish-English dual language learners in Grades 4 and 5 (n = 165). We focus on cross-disciplinary CALS, operationalized as sets of high-utility lexical, syntactic and discourse resources prevalent in school texts. This study finds that Spanish and English CALS are positively and significantly related, and, further, that both sets of skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 88 publications
0
19
1
1
Order By: Relevance
“…El constructo de Habilidades Clave del Lenguaje Académico (CALS) es un conjunto completo y claramente definido de habilidades de lenguaje que han demostrado ser útiles para predecir y apoyar la comprensión lectora de textos académicos en inglés por parte de estudiantes monolingües y bilingües inglés-español Phillips Galloway, Uccelli, Aguilar, & Barr, 2020;Uccelli & Meneses, 2015;Uccelli et al, 2015a). En 2015, Uccelli y sus colegas definieron los siguientes dominios dentro de CALS: 1) descomponer palabras complejas; 2) comprender oraciones complejas; 3) conectar ideas; 4) reconocer temas; 5) organizar textos argumentativos; 6) conciencia del registro académico.…”
Section: Evaluar Las Habilidades De Lenguaje Académico Y De Vocabulario Académicounclassified
“…El constructo de Habilidades Clave del Lenguaje Académico (CALS) es un conjunto completo y claramente definido de habilidades de lenguaje que han demostrado ser útiles para predecir y apoyar la comprensión lectora de textos académicos en inglés por parte de estudiantes monolingües y bilingües inglés-español Phillips Galloway, Uccelli, Aguilar, & Barr, 2020;Uccelli & Meneses, 2015;Uccelli et al, 2015a). En 2015, Uccelli y sus colegas definieron los siguientes dominios dentro de CALS: 1) descomponer palabras complejas; 2) comprender oraciones complejas; 3) conectar ideas; 4) reconocer temas; 5) organizar textos argumentativos; 6) conciencia del registro académico.…”
Section: Evaluar Las Habilidades De Lenguaje Académico Y De Vocabulario Académicounclassified
“…Studies increasingly have revealed how teaching language to talk about language (e.g., metalanguage) supports students’ awareness of the functions of academic language to facilitate text comprehension (e.g., Schleppegrell, 2013). Other studies have investigated how learners’ own metalanguage and metalanguage drawn from systemic functional linguistics (e.g., genre, passive voice) and literary criticism (e.g., terms from feminist literary or cultural studies) can be used to problematize, resist, and transform ways of using academic language (Harman & Khote, 2018; Phillips Galloway et al, 2020). In the example above, students made use of taught metalanguage (e.g., the phrase “authoritative perspective”) and student‐generated metalanguage (e.g., “givin’ impressions that you’re knowing something”).…”
Section: (Re)conceptualizing Academic Language Comprehension: Implicamentioning
confidence: 99%
“…Studies of multilingual students educated in English‐only U.S. classrooms have revealed a similar pattern: CALS contribute significant variance to students’ text understanding (Phillips Galloway & Uccelli, 2019). Studies of learners educated in U.S. dual‐language Spanish–English school settings have further found that CALS measured in both Spanish and English contribute unique variance to students’ English text comprehension (Aguilar, Uccelli, & Phillips Galloway, 2020; Phillips Galloway, Uccelli, Aguilar, & Barr, 2020). Linked with the idea that stores of language knowledge are interdependent, these studies indicated that both Spanish and English CALS are positively related, yet each also contribute uniquely to explain the variability in dual‐language learners’ English reading comprehension.…”
Section: Readers’ Academic Language Skills and Social Practices: Three Key Understandingsmentioning
confidence: 99%
“…At the upper-elementary level, H. Hwang and Duke (2020) and Phillips Galloway et al (2020) offer insight into predictors of English reading comprehension, with a focus on the role of prior knowledge and academic language skills, respectively. H. Hwang and Duke’s secondary data analysis—utilizing the ECLS-K national data set—focused on ELs from various language backgrounds and monolingual English-speaking peers.…”
Section: The Understudied Role Of Language Comprehensionmentioning
confidence: 99%